Effect of Thrombomodulin on the Molecular Recognition and Early Catalytic Events in Thrombin-Protein C Interaction - De Cristofaro, Raimondo (Thrombosis and Haemostasis, 1996)
A viscosity perturbation method allowed to compute the second order rate constant, k±15 for the formation of thrombin-Protein C complex, both in the absence and presence of thrombomodulin (TM) at pH 8.00 and 37° C. In the absence of TM the second order rate constant was found equal to 7.9 ± 0.6 × 103 M-1 sec-1, whereas it was enhanced to 9.9 ± 0.4 × 104 M-1 s-1 by a saturating (100 nM) TM concentration. Addition of 5 mM Ca++ to solution containing 100 nM TM induced a further increase of k+1 value up to 7.3 ± 0.5 × 105 M-1 s-1. Moreover, it was demonstrated that the thrombin-PC complex undergoes the acy-lation reaction more rapidly than it dissociates to form free thrombin and substrate (stickiness ratio = 2.4 ± 0.9). This tendency is even favored when thrombin is bound to TM both in the absence and presence of Ca++ (stickiness ratio = 9 ± 6 in the absence of Ca++ and 16 ± 10 in the presence of Ca++). Altogether these results demonstrate that TM is able to positively affect both the molecular encounter and the kinetics of the early catalytic events of the thrombin-Protein C interaction.